PENGARUH EFEKTIVITAS SUPERVISIOR TERHADAP PENINGKATAN DAN PENGEMBANGAN KARYAWAN PADA LEMBAGA KEUANGAN DI KOTA BANDUNG - Aan Hardiyana; Nenny Rinawati; Retno Resawati (STMIK Mardira Indonesia, Bandung, 2020)
The complexity of employee behavior in an organizational environment causes management to take management steps effectively. One way to increase employee effectiveness is to optimize and develop organizational members so that it will have an impact on output following the targets that have a plan. The population in this study were employees of financial institutions in the city of Bandung. The approach used is a survey approach where the sample to use is 150 employees of supervisors and employees who work in financial institutions in Bandung City. To answer the research hypothesis, the data analysis technique used component-based SEM Partial Least Square analysis. This study develops a model by filling the theoretical gap where there has been no research that has tested the effectiveness of supervisors on simultaneous employee improvement and development. The results showed that the fit model affected the effectiveness of supervisors on employee improvement and development. Implications of research results.Keywords : Supervisor Effectiveness, Job Involment, Work Engagement.